INTERNALISASI BUDAYA ORGANISASI DI POLITEKNIK KETENAGAKERJAAN - Ningrum, Tuti; Izhatullaili, Izhatullaili (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
Organizational culture is an important aspect to increase organizational commitment and performance. The internalization process is not only interpreted as a socialization process, but it is interpreted as values ​​applied as guidelines for behavior. The purpose of this study is to find out how the process of internalizing organizational culture at Politeknik Ketenagakerjaan. This study used descriptive qualitative method. Data analysis was obtained through data collection techniques. Those are observation and interviews. Based on the observation and interview developed from the interview guide, empirical information about the object of research was obtained. Then, it is processed and interpreted as a result of the research. Based on the result of this study, there are aspects of cultural rewards that become a factor inhibiting the internalization process of organizational culture ​​at Politeknik Ketenagakerjaan.